Food security policy innovation in Bandung City - Jeremia Gom Gom Parulian Simanjuntak; Oktovina Hanani Krisitin Monim; Muthia Zahira Rachman; Virgilia Karin Novita; Cindy Kartini Yubawa (Universitas Merdeka Malang, 2023)
During the COVID-19 pandemic, food security is a major concern, there arerapid changes and uncertainty in the situation. The pandemic has a negativeimpact on national food security, Indonesia’s food security index was 61.4percent in 2020, but it drops to 59.2 percent in 2021. Meanwhile, Bandung isnot a food production location based on regional features, as 96 percent of foodis obtained from areas beyond the city limits. Furthermore, the lack of agricul-tural land makes food availability in Bandung vulnerable, posing a threat tothe city’s food security. This study aims to analyze policy innovations used bythe government to address food security issues. This study is used the policyinnovation approach to assess the policies implemented by the Bandung CityGovernment in the food sector. A case study technique is used to analyze thisphenomenon utilizing qualitative approaches. Interviews, observations, andliterature reviews is used to gather data. The results show that although thereare still shortcomings, the Bandung City government has implemented inno-vations in maintaining food security. Food and Agriculture Security Depart-ment of Bandung still must make improvements in the areas of training anddevelopment for the community to support food security in Bandung.